Field Performance of a 17 m-High Reinforced Soil Retaining Wall. Issue 5 (2001) - Runser, D.J.; Fox, P.J.; Bourdeau, P.L.
Abstract : A 17 m-high steel strip reinforced soil retaining wall was instrumented to compare field measurements with predictions given by the design guidelines of the American Association of State Highway and Transportation Officials (AASHTO) 1996 Standard Specifications and the AASHTO 1999 Interim Revisions. The AASHTO models were conservative with respect to external lateral earth pressures and lateral earth pressures on the facing panels. On average, the AASHTO 1996 and 1999 models overestimated lateral pressure at the facing by 94 and 142%, respectively. Measured values of foundation bearing stress were generally in good agreement with values calculated using soil unit weight and depth, except that the average force from the facing panels on the leveling pad was twice that of the weight of the panels themselves. This discrepancy is attributed to shear stress on the back of the facing panels and vertical loads transferred to the panels through the strip connection clips. The location of the zone of maximum strip tension was in good agreement with the assumed failure surface. On average, the AASHTO 1996 and 1999 models underestimated maximum strip tensions by 17 and 8% and overestimated strip connection tensions by 127 and 154%, respectively. Finally, the apparent soil-reinforcement friction coefficient for the ribbed steel strips exceeded values specified in the AASHTO models by an average of 132%.